“Deixe-me ser teu templo de promiscuidade”: consumo escópico do excesso nas performance-vida e performance post mortem de Hija de Perra - Santos, Thiago Henrique Ribeiro dos (2020)
This research investigates the audiovisualities of the bizarre Chilean performer Hija de Perra (1980-2014). The general objective is to analyze, through a communication and consumption perspective, the public performance of that artist and to understand the consumption-related and expressive contexts of her digital tracks, with a specific focus on the audiovisualites available on the YouTube video platform. The specific objectives are: a) to build a method that uses digital traces and their circulation and consumption dynamics to research contemporary objects/subjects in the urban and post-mass interstitial areas; b) to describe some different dimensions of the archived video performances and their specificities; c) to identify the aesthetic-political bricolages of the archived performances’ audiovisual poetics, as well as problematizing their configurations and characteristics; d) to investigate the consumption of audiovisualities in the post-massive socio-cultural context and how it occurs, specifically, with regard to the Hija de Perra archive. The method utilized for such purpose was cartography, which was led by this researcher's gaze and the traumatic encounters between him and Hija de Perra’s audiovisualities. Under a category named “theoretical orgies”, the multidisciplinary character of Communication is employed to compare authors from different fields, such as communication, psychoanalysis, sociology and performance and consumption studies. As a result, we find that Hija de Perra's performance of audiovisualities can be divided into two interconnected dimensions: performance-life and post-mortem performance. The first one refers to the inseparability of art and life, as articulated by the artist's performance during her incarnated time in this world. Among the specificities of this performative dimension, we identified the the liminality of self-narrative, mobilization of abject affections and the symbolic exorcism of coloniality. The post-mortem performance, in turn, is composed by the artist’s digital tracks left in the world, her communicational materialities. Given their capacity to affect, especially in the audiovisualities field, they constitute performances in themselves and, once considered altogether as a whole audiovisual body, they can be considered yet another performance which we name post-mortem. Its particularities include deadly virality, death transgressions, reactions through videoclip and presence production. Finally, the "excess" is seen as a category of experimentation, which allows us to connect this artist's performances to the consumption of excess in its audiovisual and symbolic dimensions. For it occurs exclusively through the gaze, we name it “scopic consumption of excess”. Shards of excess and their produced modes of presence, when articulated in different intensities, are described and analyzed to compose Hija de Perra’s trans-aesthetic of the excess in a camp and grotesque bricolage. Finally, we argue that this artist's performance-life and post-mortem performance are mobilizers of an eroptic communication, linking at once the seer to the image, and going through them by self-dissolving energy flows, and also external to the contentional barriers of language and all attempts at interpretation. An experience of feeling, not of attributing meaning.